Direct solution of second-order BVPs by homotopy-perturbation method (Penyelesaian Secara Langsung MNS Berperingkat-Dua Melalui Kaedah Homotopi-usikan) - Abdulaziz, O.; Chowdhury, Md. Sazzad Hossien; Hashim, Ishak; Momani, Shaher Mohammad (Penerbit UKM, 2009)
In this paper, systems of second-order boundary value problems (BVPs) are considered. The applicability of the homotopy-perturbation method (HPM) was extended to obtain exact solutions of the BVPs directly.